Ageing and obesity similarly impair antibody responses. (1st August 2016) - Frasca, D.; Diaz, A.; Romero, M.; Blomberg, B. B.
Summary: Ageing is characterized by increased low‐grade chronic inflammation, which is a significant risk factor for morbidity and mortality of elderly individuals. Similar to ageing, obesity is considered to be an inflammatory predisposition associated with chronic activation of immune cells and consequent local and systemic inflammation. Both ageing and obesity are characterized by reduced innate and adaptive immune responses. This review focuses on B cells, how they may contribute, at least locally, to low‐grade chronic inflammation in ageing and obesity and on the mechanisms involved.